Buffalo soldiers : fighting on two fronts [videorecording (DVD)] - Holley, Dru; Evans, Dan (Daniel D.); Multer-Wellin, Barbara; Berkshire, Ayanna (PBS Distribution, 2023)
Explores the often-contradictory role played by Black soldiers throughout American history. Established by Congress, the 14th Amendment of 1886 promised citizenship in exchange for enlistment, prompting many African American men to serve.